Reflective practice in the teaching practicum program: Pre-service English teachers’ reflections - Nurhidayah, Mila Ida; Wirza, Yanty (Journal of Applied Studies in Language, 2024)
Reflective practice has gained significant importance in various professional educational settings. There has been a surge in research conducted on reflective practice across different fields, including English teaching, which indicates an increasing interest in this area. This study explores how pre-service English teachers reflect on their teaching journey, spanning from their initial teaching experiences to their future aspirations. Furthermore, these participants have undergone a teaching practicum program at public high schools in Bandung, Indonesia. In addition, the study uses a qualitative approach through a narrative inquiry design, with three pre-service English teachers participating in interviews to share their experiences. Before the interviews, the participants were required to complete a narrative framework. In addition, the collected data are analyzed through thematic analysis. The findings demonstrate how reflection in teaching practice can positively impact the teaching performance of pre-service English teachers by enhancing their instructional strategies, addressing areas for improvement, and promoting continuous professional development. In conclusion, this study highlights the significance of reflective practice in the field of English teaching and offers insights into its benefits for pre-service teachers. It emphasizes the importance of ongoing reflection to improve teaching effectiveness and enhance the overall quality of education.